The effect of extracorporeal shock wave lithotripsy in the management of idiopathic gallstones in children - Seyed Abdollah Mousavi; Hasan Karami; Ayub Barzegarnejad (Wolters Kluwer Medknow Publications, 2014)
Objective: The most common etiology for gallstones in children is hemolytic diseases; however, the prevalence of nonhemolytic gallstones, which are mostly idiopathic, is increasing. Several studies concerning the treatment of gallstones with respect to the influence of extracorporeal shock wave lithotripsy (ESWL) have been conducted in adults, but not to the same extent in children. Therefore, this study attempted to examine the effects of lithotripsy on idiopathic gallstones in children. Materials and Methods: In this study, 12 children, all of whom were under 12 years of age and diagnosed with idiopathic gallstones, were treated with ESWL. The average age of the children examined in this study was 6.5 years (range 3-11 years). Patients were treated with 2500-3000 shockwaves per session. The number of shockwaves was 90 shocks/min and the impulse intensity ranged from 10 to 12 kV. The final goal was the fragmentation of stones in pieces with less than 3 mm in dimension. Patients were followed up for 6-30 months. Results: A total of 12 patients were treated with ESWL for 14 rounds. In three patients, complete fragmentation occurred within the first trial and was cleared. The nine remaining patients underwent ESWL 10 times in which an acceptable change in the gallstone's condition was not observed. Five of the patients underwent surgery. The chemical composition of the gallstones showed that the dominant element in them was calcium. Conclusions: Our findings show that performing ESWL can be effective in some children. Further studies with larger population are recommended. Furthermore, it seems increasing the voltage intensity and frequency as conducted in adults accompanied with biliary acids prescription can be effective in children.